European bird declines: Do we need to rethink approaches to the management of abundant generalist predators?. Issue 10 (20th July 2020) - McMahon, Barry J.; Doyle, Susan; Gray, Aimée; Kelly, Seán B. A.; Redpath, Steve M.
Abstract: Bird species are declining across Europe. Current European policy, that is, the Birds and Habitats Directives, focus on habitat management as a way of halting the declines. This paper explores the role of predation in causing bird population declines and asks if we need to reconsider our approach to the management of generalist predators. We analysed bird population trends and distribution changes across Europe, Britain and Ireland, reflecting an increasing gradient of generalist predator abundance (principally red fox Vulpes vulpes and species of the family Corvidae ). We tested if ground‐nesting bird species, considered more vulnerable to predation, were in greater decline compared to other nesting strategies. We also compared Annex I designated species to non‐designated species as a proxy for habitat management. We found that across Europe, 74% of ground‐nesting bird species were in decline, compared to 41% of other species. This was especially evident in Britain, where the pattern was 66% compared to 31%, and in Ireland, 71% compared to 20%. Ground‐nesting species were significantly more likely to be declining than other species. These patterns are consistent with the idea that population declines are at least partially related to the increased abundance of generalist predators. In Britain, ground‐nesting species were less likely to be in decline if covered by Annex I designation. However, in Europe and Ireland, Annex I status did not mitigate the effect of nesting strategy. Policy implications . Current legislation is clearly insufficient to prevent widespread declines in ground‐nesting birds, and this is the case across Europe, in Britain and Ireland. Ignoring the role of generalist predators in modern landscapes may lead to further declines and losses. We urgently need large‐scale experiments to establish causality in the impact of generalist predators on ground‐nesting birds in different landscapes. If we value our ground‐nesting bird species, consideration needs to be given to the control of widespread generalist predators, at least until landscapes are restored. Abstract : Current legislation is clearly insufficient to prevent widespread declines in ground‐nesting birds, and this is the case across Europe, in Britain and Ireland. Ignoring the role of generalist predators in modern landscapes may lead to further declines and losses. We urgently need large‐scale experiments to establish causality in the impact of generalist predators on ground‐nesting birds in different landscapes. If we value our ground‐nesting bird species, consideration needs to be given to the control of widespread generalist predators, at least until landscapes are restored.